THE PREVALENCE OF CARBAPENEM-RESISTANT ENTEROBACTERIACEAE INFECTIONS IN HOSPITALIZED PATIENTS AT INKOSI ALBERT LUTHULI CENTRAL HOSPITAL: A RETROSPECTIVE COHORT STUDY IN DURBAN, SOUTH AFRICA. - Fuyane, Denzel; Shangase, Simangaliso (Student’s Journal of Health Research Africa, 2024)
Introduction Carbapenems are antibiotics that fall within the beta-lactam antibiotic family utilized against multidrug-resistant Gram-negative microorganisms due to their broad range of antimicrobial action. However, there has been a rise of carbapenemase-producing organisms that are resistant to carbapenems making the treatment of infections difficult. Aims and Objectives The primary aim of this research is to investigate the occurrence of carbapenem-resistant Enterobacteriaceae (CRE) infections among patients receiving hospital care in Durban, South Africa, and also ascertain the predominant organisms causing these infections and evaluate the efficacy of available treatment options. Methodology This was a quantitative, retrospective cohort study that investigated carbapenem-resistant Enterobacteriaceae among 534 patients of all genders and age groups. The procedure involved detecting microorganisms in a patient’s blood and their susceptibility patterns. Data, spanning from January 1, 2021, to December 31, 2021, was retrospectively collected through medical laboratory reports. Results Results showed a total of 21.8% of cases were resistant to at least one of the three carbapenems (ertapenem, imipenem, or meropenem), with Klebsiella spp. This is the most prevalent (62.7%), followed by Enterobacter spp.(18.9%) and Escherichia coli (10.8%). Furthermore, the results showed that there was no significant difference between ertapenem and imipenem in terms of their efficacy against CRE. However, meropenem demonstrated the maximum effectiveness against CRE. Conclusion Klebsiella spp. Emerged as the predominant microorganisms, followed by Enterobacter spp. and Escherichia coli. Evaluating the effectiveness of antimicrobial drugs revealed that meropenem consistently demonstrated superior efficacy, particularly against Klebsiella spp. andEnterobacter spp., with imipenem also showing notable effectiveness, especially against Escherichia coli. Recommendations These include optimizing antimicrobial use through careful prescribing, providing education and training for healthcare personnel, expanding resistance surveillance, and fostering collaboration and data sharing among healthcare facilities to address the local and global challenges of CRE infections.